Comparison of Morphological Differences Among Four Species of the Genus Thymallus - Kai MA; Guangxiang TONG; Lanlan ZHANG; Huizhi SUN; Mingliang WEI; Cheng ZHAO; Baoquan HE; Jiasheng YIN; Yongquan ZHANG (Science Press, PR China, 2024)
The genus Thymallus, belonging to the Salmoniformes, Salmonidae and Thymallinae, is distributed in three main areas in China, namely, the Irtysh River Basin, the Heilongjiang River Basin and the Yalu River Basin. Research has shown that the diversity of extant Thymallus in China is much higher than that in the vast European and North American regions, but the taxonomic results of some species are still controversial. Among them, those whose taxonomic status has been clarified and whose nomenclature is not controversial are T. arcticus, T. grubii and T. tugarinae, and the one that is still controversial is T. yaluensis. Named by Mori in 1928, T. yaluensis is mainly distributed in the Yalu River Basin and is geographically isolated from the T. arcticus, T. grubii and T. tugarinae. In 2007, a study on the comparison of countable traits of Thymallus found that the countable traits of the T. yaluensis were in the middle between the T. grubii and T. tugarinae, and the validity of the taxonomic status of T. yaluensis has been formally questioned ever since; in 2008, a study using mitochondrial DNA control region sequences to study the evolutionary relationships of fishes in the genus Thymallus pointed out that the T. yaluensis is synonymous with the T. grubii. In 2016, researchers used mitochondrial genome data to confirm once again that there was no difference between the T. yaluensis and the T. grubii. However, this conclusion does not seem to be accepted by the academic community, and in recent years, there are still some scholars who regard the T. yaluensis as an independent species. Morphological methods are the most commonly used methods in species identification, which can be categorized into traditional morphological method and framework measurement method. The traditional morphological method mainly analyzes the horizontal and vertical traits of the fish body, and it is mostly limited to the head and tail traits, which can't measure the whole surface of the fish body comprehensively. The framework measurement ...